2008
DOI: 10.1063/1.3040074
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of NO(A Σ2+) with rare gas atoms: Potential energy surfaces and spectroscopy

Abstract: We present the results of an ab initio study of the interaction of electronically excited NO(A (2)Sigma(+)) with rare gas (Rg) atoms. The bound states of each NO(A)-Rg species are determined from potential energy surfaces calculated at the RCCSD(T) level of theory. Making use of the NO(X (2)Pi)-Rg vibrational wavefunctions, we then simulate electronic spectra. For NO-Kr and NO-Xe we obtain good qualitative agreement with the previously published experimental spectra. For NO-Ar, the shallowness of the surface g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
86
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(101 citation statements)
references
References 54 publications
11
86
4
Order By: Relevance
“…31 In particular, B3LYP-D3 calculations predicted a minimum energy structure with a Ar-N-O angle of 30 o , whereas high level calculations and experiment find the angle to be 0 o . [45][46][47] A further shallow minimum is predicted for a Ar-N-O angle of 180 o , in agreement with experiment and previous calculations. [45][46][47] This is illustrated in Figure 7 that shows the interaction potential at the B3LYP-D2 level, which closely resembles the B3LYP-D3 one.…”
Section: Variation Of the Dispersion Correctionsupporting
confidence: 89%
See 1 more Smart Citation
“…31 In particular, B3LYP-D3 calculations predicted a minimum energy structure with a Ar-N-O angle of 30 o , whereas high level calculations and experiment find the angle to be 0 o . [45][46][47] A further shallow minimum is predicted for a Ar-N-O angle of 180 o , in agreement with experiment and previous calculations. [45][46][47] This is illustrated in Figure 7 that shows the interaction potential at the B3LYP-D2 level, which closely resembles the B3LYP-D3 one.…”
Section: Variation Of the Dispersion Correctionsupporting
confidence: 89%
“…[45][46][47] A further shallow minimum is predicted for a Ar-N-O angle of 180 o , in agreement with experiment and previous calculations. [45][46][47] This is illustrated in Figure 7 that shows the interaction potential at the B3LYP-D2 level, which closely resembles the B3LYP-D3 one. Also shown is an analogous potential energy surface computed with B3LYP-D2 with modified (increased by a factor of 2 for nitrogen and oxygen) van der Waals radii.…”
Section: Variation Of the Dispersion Correctionsupporting
confidence: 89%
“…Recent calculations 23 confirm that the NO-Ar X state has a "T" structure, 3 while the à state is near linear. 6 The NO-Ar bond length is substantially increased from the X to à states. 3,6,23 There is, therefore, poor overlap between the ground vibrational levels in the two electronic states.…”
Section: How Can X States With Low Population Contribute Significamentioning
confidence: 97%
“…In contrast, the à state is linear, 4,5 with the most recent results revealing that the argon is situated adjacent to the nitrogen atom. 6 Because of the large geometry change between the X and à states, transitions to the bound region near the origin are very weak and it was some time before they were observed. The first investigation of the bound-bound à 2 ⌺ ← X 2 ⌸ transition was of quite low resolution but revealed that structure was observable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation